2015
DOI: 10.1016/j.cell.2015.07.016
|View full text |Cite
|
Sign up to set email alerts
|

An Essential Role of the Mitochondrial Electron Transport Chain in Cell Proliferation Is to Enable Aspartate Synthesis

Abstract: Summary The mitochondrial electron transport chain (ETC) enables many metabolic processes, but why its inhibition suppresses cell proliferation is unclear. It is also not well understood why pyruvate supplementation allows cells lacking ETC function to proliferate. We used a CRISPR-based genetic screen to identify genes whose loss sensitizes human cells to phenformin, a complex I inhibitor. The screen yielded GOT1, the cytosolic aspartate aminotransferase, loss of which kills cells upon ETC inhibition. GOT1 no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

73
1,188
3
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,162 publications
(1,272 citation statements)
references
References 59 publications
73
1,188
3
8
Order By: Relevance
“…Light also could inhibit de novo purine synthesis by decreasing the amount of aspartate in the cell. Recent studies showed that decreases in nucleotide levels correlate with reduced synthesis of aspartate (52)(53)(54)(55)(56). These are reasonable mechanisms by which light could regulate de novo purine synthesis.…”
Section: Illumination Influences Nucleotide Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Light also could inhibit de novo purine synthesis by decreasing the amount of aspartate in the cell. Recent studies showed that decreases in nucleotide levels correlate with reduced synthesis of aspartate (52)(53)(54)(55)(56). These are reasonable mechanisms by which light could regulate de novo purine synthesis.…”
Section: Illumination Influences Nucleotide Metabolismmentioning
confidence: 99%
“…Recent studies of metabolism in other types of cells also concluded that anabolic activities of mitochondria can even be more essential than ATP synthesis (53,55).…”
Section: Control Of Metabolism By Signalingmentioning
confidence: 99%
“…The importance for aspartate metabolite in addition to alpha-ketoglutarate for survival of HDAC5-depleted cells is quite interesting. The role of this amino acid and its interaction with glutamine/glutamate and TCA cycle metabolism is becoming more and more studied in cancer cells [33][34][35][36] and this should be also further addressed in the context of HDAC5 depletion.…”
Section: Discussionmentioning
confidence: 99%
“…The TCA cycle could also be required during rapid growth, even when ATP production by OXPHOS is not necessary, to maintain synthesis of biomolecules such as glutamate or aspartate. A recent study has reported that an essential function of respiration in proliferating cells is to support aspartate synthesis [68,69]; minimal flow through the TCA cycle therefore needs to be maintained even when the ETC is repressed. Iron deficiency also leads to repression of transcripts encoding ETC subunits, but in this condition the succinate dehydrogenase complex is also strongly repressed [70,71] (Additional file 2: Figure S16).…”
Section: Discussionmentioning
confidence: 99%